Pengaruh Jumlah Penduduk, Inflasi, dan Kemiskinan terhadap Pengangguran di Provinsi Sumatera Barat - Nurul Sifa; Nurfahmiyati (UNISBA Press, 2022)
Abstract. Unemployment is one of the phenomena or employment problems that occurs in all developing countries, including Indonesia, especially in the province of West Sumatra. Unemployment is a problem that is faced together socially as well as a personal problem that is psychological for the person concerned. If the handling of the unemployment problem is not optimal, it will have an impact on increasing the number of poverty so that it can make the community less prosperous. Unemployment is a very complex problem because it affects and is influenced by many factors that interact with each other following a pattern that is not always easy to understand. Based on this phenomenon, the problems in this study are formulated as follows: (1) Is there an influence between the population on unemployment in West Sumatra Province? (2) Is there any influence between inflation and unemployment in West Sumatra Province? (3) Is there any influence between poverty and unemployment in West Sumatra Province?. Researchers used quantitative methods with time series data. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS) and journals as supporters. Regression analysis method using Ordinary Least Square (OLS) method. In addition, the Classical Assumption Test and the Statistical Test were conducted, where all of these tests used the Eviews 7 program tool. The results of this study were that all variables consisting of population, inflation, and poverty had an insignificant positive effect on unemployment. Abstrak. Pengangguran menjadi salah satu fenomena atau permasalahan ketenagakerjaan yang terjadi di semua negara berkembang, tidak terkecuali di Indonesia khususnya di Provinsi Sumatera Barat. Pengangguran menjadi permasalahan yang dihadapi bersama secara sosial sekaligus menjadi permasalahan pribadi yang bersifat psikologis bagi yang bersangkutan. Jika penanggulangan masalah pengangguran tidak optimal, maka akan berdampak pada peningkatan jumlah kemiskinan sehingga dapat membuat masyarakat menjadi tidak sejahtera. Pengangguran merupakan masalah yang sangat kompleks karena mempengaruhi sekaligus dipengaruhi oleh banyak faktor yang saling berinteraksi mengikuti pola yang tidak selalu mudah untuk dipahami. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apakah terdapat pengaruh antara jumlah penduduk terhadap pengangguran di Provinsi Sumatera Barat? (2) Apakah terdapat pengaruh antara inflasi terhadap pengangguran di Provinsi Sumatera Barat? (3) Apakah terdapat pengaruh antara kemiskinan terhadap pengangguran di Provinsi Sumatera Barat?. Peneliti menggunakan metode kuantitatif dengan data time series. Data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) dan jurnal sebagai pendukung. Metode analisis regresi dengan metode Ordinary Least Square (OLS). Selain itu dilakukan Uji Asumsi Klasik dan Uji Statistika, dimana semua pengujian tersebut digunakan alat bantu program Eviews 7. Hasil dari penelitian ini adalah seluruh variabel yang terdiri dari jumlah penduduk, inflasi, dan kemiskinan berpengaruh positif terhadap pengangguran secara tidak signifikan.